Oral health behaviors in a sample of Portuguese adolescents: an educational issue - Veiga, Nélio (2014)
Introduction: Oral health education is an important issue that should be given to children and adolescents, allowing the acquisition of correct oral health behaviors. The objective of this study was to determine the prevalence of oral health behaviors among a sample of portuguese adolescents and verify the association with socio-demographic factors, in order to analyze the main needs related with oral health education to improve oral health status among adolescents. Methods: A cross-sectional study was designed with a sample of 447 adolescents aged 12 to 19 years old, attending a public school in Sátão, Portugal. A self-administered questionnaire was applied questioning about socio-demographic factors and oral health behaviors to each adolescent in the classroom. Prevalence was expressed in proportions and crude odds ratio (OR) with 95% confidence intervals (CI) were used to measure the strength of association between oral health behaviors and socio-demographic factors. Results: The prevalence of tooth brushing (twice-a-day or more) was 90.6%. Five point eight percent of adolescents reported daily flossing, more frequent among female gender (female, OR = 2.03, 95% CI = (1.35 to 3.05)) and adolescents older than 15 years (>15 years, OR = 1.90, 95% CI = (1.24 to 2.92)). Sixty-seven percent had at least one dental appointment in the previous twelve months. The prevalence of dental appointments was associated with the father’s professional situation (unemployed, OR = 0.33, 95% CI = (0.17 to 0.65)) and crowding index (>1, OR = 0.4, 95% CI = (0.16 to 0.98)). Thirty-two point nine percent of adolescents referred having at least one episode of dental pain during their lives. Conclusion: Considering the results of the present study that show the need of improvement of some aspects related with oral health among adolescents, oral health community programs and primary preventive strategies, such as improvement of oral health education in schools should be considered in order to reduce the risk level of oral diseases and develop better oral health behaviors.